Psychometric Properties of Identity Style Inventory-5 Indonesian Version: Factor Structure, Reliability, and Criterion Validity - Muttaqin, Darmawan (Jurnal Psikologi, 2021)
This research evaluated the psychometric properties of the Identity Style Inventory-5 (ISI-5) Indonesian version using 763 adolescents aged 18-21 years. The evaluation process was carried out by examining the factor structure, reliability, and criterion validity using confirmatory factor analysis, composite reliability, and by correlating with other measuring instruments. The analysis results indicated that the ISI-5 version's factor structure with three factors of identity style and one identity commitment is fit with the data and has good internal consistency. The correlation between this version and other measuring instruments proves that it has fairly good criterion validity. The results showed that the ISI-5 Indonesian version is a valid and reliable instrument for measuring Indonesian adolescents' identity style and commitment.